Virtual Instrument for Screening and Visual Function Recovery for Preschool or Primary School Children - BRAUN Barbu Criatian; DRUGĂ Corneliu Nicolae; ȘERBAN Ionel (My University, 2020)
In the paper there is presented a stage of research in order to improve screening and casuistic procedures, applied in the pediatric field, specific especially for visual function. During the current research phase, a software interface was designed, programmed and tested, aiming both visual screening and its use for recovery procedures, in the case of detected preschool children with visual problems. The procedure by which the answers of preschool children to different tests on visual function can be evaluated is “serious games” type, which should be an attractive one for the child (with different chromatic effects on computer, tablet, smart-phone). etc.). On the other hand, it is intended both to gradually develop the skills related to visual function and to support the doctor or pediatric optometrist in assessing quickly and objectively whether the answers to tests recommend a normal situation or a pathological case that requires treatment. From the point of view of evaluation procedure via virtual instrumentation, two main aspects have been considered: testing and/or training of visual memory, as well as testing and/or training of visual acuity in preschool children, for which visual sense is still developing.
Keywords: children; screening; virtual instrument; visual